1973
DOI: 10.1115/1.3450004
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Laminar Free and Forced Convection between Finite Vertical Parallel Plates

Abstract: Approximate analytical solutions are presented for constant-property laminar free- and forced-convection flows between finite vertical parallel plates. For free convection, the thermal boundary conditions considered include the thermally symmetric channel with uniform wall temperature or step change in wall temperature and the unsymmetric channel with uniform but unequal wall temperatures. For forced convection and combined free and forced convection, the thermally symmetric and uniform thermal boundary condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The physically more suitable condition was also indicated by Quintiere and Mueller [6] and El-Shaarawi and Sarhan [7] by applying the usual Bernoulli equation.…”
Section: Inlet Pressure Conditionmentioning
confidence: 92%
“…The physically more suitable condition was also indicated by Quintiere and Mueller [6] and El-Shaarawi and Sarhan [7] by applying the usual Bernoulli equation.…”
Section: Inlet Pressure Conditionmentioning
confidence: 92%
“…Many studies of mixed convection in vertical slots and annuli have adopted the parallel flow assumptions (Shumway and McEligot, 1971;El-Shaarawl and Sarhan, 1980;Kim, 1985;Hashimoto, Akino and Kawamura, 1986;Quintiere and Mueller, 1973;Habchi and Acharya, 1986;, and ignored the possible hydrodynamic instabilities that can lead to increased mixing of the fluid. Thus, the results obtained without accounting for these effects will tend to underpredict the actual heat transfer rates.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the 2d simulation have provided a acceptable prediction for the problem up to Rayleigh 1 × 10 7 while greater than that value the flow becomes three-dimensional and turbulent. This result seems to be inconsistent to the conclusion stated by Quintiere and Mueller [8]. Fossa et al [9] has introduced a study on natural convection between two parallel walls.…”
Section: Introductionmentioning
confidence: 78%